Dialogic voice: a pragma-dialectical approach to R. G. Mugabe's ceremonial speeches - Jakaza, Ernest (John Benjamins Publishing Company, 2016)
This chapter critically examines Mugabe's two speeches. The one he delivered at the United Nations (UN) climate change summit that was held in Copenhagen in 2009 and the other one he delivered at the 2008 Zimbabwean independence celebrations. The chapter argues that not only conversations with explicit participants can he regarded as argumentative (van Eemeren, 2010). Thus, to achieve the purpose, the pragma-dialectic theory of argumentation is employed. The analysis of the speeches show how Mugabe utilised the podium to dialogically interact with the audience, both outside and inside, persuasively inviting them to align with him (speaker) and disalign with the 'negative' voices. The analysis also confirms that stance taking and value positioning is a factor in argumentative discourse.